2004
DOI: 10.1210/en.2003-1319
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Exercise Endurance in Interleukin-6-Deficient Mice

Abstract: IL-6 is produced and released in large amounts from skeletal muscle during prolonged exercise in both mice and humans, but there are few data indicating the biological significance of this. IL-6 exerts metabolic effects such as stimulating energy expenditure and reducing body fat mass. We have now investigated the effects of IL-6 deficiency on exercise endurance and energy expenditure in preobese and obese IL-6-deficient (IL-6(-/-)) mice. Four-month-old preobese and 7-month-old obese IL-6(-/-) male mice backcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
96
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 35 publications
19
96
2
2
Order By: Relevance
“…This is consistent with reports that a deficiency of IL-6 in mice results in reduced exercise endurance (Wallenius et al 2002;Faldt et al 2004). In addition, we observed (a) evidence of impeded glycogen recovery after R+G+, and (b) no R+G+-induced increase of MM Glut4 mRNA in IL-6-KO mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with reports that a deficiency of IL-6 in mice results in reduced exercise endurance (Wallenius et al 2002;Faldt et al 2004). In addition, we observed (a) evidence of impeded glycogen recovery after R+G+, and (b) no R+G+-induced increase of MM Glut4 mRNA in IL-6-KO mice.…”
Section: Discussionsupporting
confidence: 93%
“…IL-6 is rapidly released into the circulation following the decline of glycogen that occurs in working skeletal muscle, and acts in a hormone-like fashion to increase systemic glucose uptake, fat oxidation, hepatic glucose production, and lipolysis (Kim et al 2008;Gusba 2009;Pedersen 2009). Indeed, a deficiency of IL-6 in mice results in reduced exercise endurance (Wallenius et al 2002;Faldt et al 2004). Hence, IL-6 is now believed to be an essential regulating factor in muscle glucose homeostasis during and after exercise (Yudkin et al 2000;Gusba 2009;Pedersen 2009).…”
mentioning
confidence: 99%
“…[27][28][29] Moreover, endogenous IL-6 seems to influence energy expenditure during exercise. 30 Interestingly, the data of recent studies indicate that the -174 C allele is associated with decreased energy expenditure 31 and slightly decreased body temperature. 14 Taken together, these results indicate that the À174 C allele of the IL-6 promoter decreases IL-6 production, which in turn results in decreased energy expenditure and accumulation of body fat.…”
Section: Discussionmentioning
confidence: 99%
“…He postulated that this effect might be mediated by IL-6. Faldt et al 21 suggested that IL-6 exerts its effect by stimulating energy expenditure and reducing body fat mass. Further, IL-6 deficient mice had reduced endurance and energy expenditure during exercise.…”
Section: Il-6 and Tnf- Alterations With Exercise In Animal Modelsmentioning
confidence: 99%